Carbon dioxide and N2 efficient electro-catalysis urea synthesis method based on electron cluster induced precipitation technology
The CoN3-CoAC/NC catalyst prepared based on electron cluster induction precipitation technology has solved the problem of insufficient activity and selectivity in the existing urea electrosynthesis technology, achieved efficient urea electrosynthesis, set records of the highest yield and Faraday efficiency, and the catalyst has a stable structure during long-term electrolysis.
Patent Information
- Application Number
- CN202411674918.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-21
AI Technical Summary
In the existing urea electrosynthesis technology, the activity and selectivity are not satisfactory, mainly because the adsorption and coupling of active intermediates are not ideal, and the catalysts at single metal atom sites are unstable during long-term electrolysis.
Using an electron cluster-induced precipitation technology, the CoN3-CoAC/NC catalyst was prepared through the crystallization-pyrolysis process of the ZIF-67 precursor. The synergistic effect of the Co cluster and the Co-N3 single atomic site was used to optimize the N2 and CO2 adsorption configuration to generate an ideal intermediate product.
The urea yield reached 20.83 mmolh-1g-1 and the Faraday efficiency was 23.73%, setting a record for urea electrosynthesis. At the same time, the current density of the catalyst was stable during continuous electrolysis for 10 hours and the structure was maintained.
Smart Images

Figure CN119506911A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalysis, and in particular to a method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology. Background Art
[0002] Global warming and environmental problems are becoming increasingly serious due to excessive emissions of carbon dioxide (CO2).
[0003] There is a renewed interest in exploring potential solutions for achieving high-value utilization of CO2. Electrochemical CO2 reduction (ECR) technology powered by renewable electricity is considered a promising technology for producing valuable carbon derivatives (such as CO, HCOOH, CH3OH, C2H4, etc.). However, the original ECR route still faces the problem of limited product variety. Urea is the most representative product of the above reaction. It is an important nitrogen fertilizer with the highest nitrogen content and is also a basic component for the manufacture of urea-formaldehyde, urea-melamine-formaldehyde resin and barbiturates.
[0004] In this context, urea electrosynthesis eliminates the stringent reaction requirements and achieves the direct conversion of inert CO2 and N2 reactants under ambient conditions, compared with the conventional thermal catalytic process (150–550 °C, 150–350 bar). For example, PdCu alloy nanoparticles (NPs) supported on TiO2 nanosheets have achieved efficient electrocatalytic urea synthesis. In addition to precious metal palladium-based catalysts, Bi-BiVO4
[24] and BiFeO3 / BiVO4 heterostructure catalysts have been developed for the co-reduction of CO2 and N2 molecules to produce urea. Apparently, the built-in electric field at the heterostructure interface enables the adsorption and activation of active molecules. Despite the encouraging progress, the activity and selectivity of urea electrosynthesis are still unsatisfactory, which may be attributed to the suboptimal adsorption and coupling of active intermediates. Therefore, the key to overcoming the above obstacles lies in the precise design of active sites to enhance the interaction between molecules and catalysts and to couple the desired intermediates in a targeted manner. In fact, increasing the number of active sites and improving the intrinsic activity of each active site are considered to be two effective strategies to promote electrocatalytic activity. More specifically, catalysts with single metal atom sites, including well-defined cobalt pyrrolidine dianhydride conducting metal-organic frameworks (Co-PMDA-2mbIM) and copper phthalocyanine nanotubes (CuPcNTs), both of which feature isolated metal active sites, have been shown to be effective for electrocatalytic urea synthesis. However, the metal atoms in single-atom catalysts are prone to migration and aggregation during long-term electrolysis due to structural instability.
[0005] In view of this, a highly efficient electrocatalytic urea synthesis method of carbon dioxide and N2 based on electron cluster induced precipitation technology is provided to overcome the above problems. Summary of the invention
[0006] The object of the present invention is to provide a method for efficiently electrocatalyzing urea synthesis of carbon dioxide and N2 based on electron cluster induced precipitation technology to solve the problems raised in the above background technology.
[0007] In order to solve the above technical problems, the present invention provides a method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology, comprising the following steps:
[0008] S1. Catalyst preparation; including precursor preparation, crystallization-pyrolysis process;
[0009] The precursor preparation includes selecting ZIF-67 with a purity of ≥99.5% as a precursor for preparing the electrocatalyst;
[0010] The crystallization-pyrolysis process involves placing the ZIF-67 precursor in a precisely temperature-controlled tube furnace for annealing;
[0011] S2. Electrocatalytic urea synthesis experiment; including experimental device construction, electrolyte and gas supply, electrochemical testing; electrochemical testing includes CoN3-CoAC / NC catalyst performance test, stability test, and comparison of catalyst performance;
[0012] S3. Reaction mechanism analysis.
[0013] Furthermore, during the crystallization-pyrolysis process, the temperature control accuracy of the tubular furnace was ±0.5°C, the heating rate was set to 5°C / min, the cooling rate was 3°C / min, the atmosphere was high-purity nitrogen, and the gas flow rate was 50 mL / min.
[0014] Further, during the crystallization-pyrolysis process, when the heat treatment time was set to 10 min, CoN4-CoAC / NC was formed.
[0015] Furthermore, during the crystallization-pyrolysis process, as the pyrolysis time increases, some Co-N bonds break to form CoN3-CoAC / NC.
[0016] Furthermore, during the crystallization-pyrolysis process, the calcination time was extended to obtain CoNP / NC containing nanoparticles.
[0017] Furthermore, the performance test of the CoN3-CoAC / NC catalyst was carried out 5 times under the voltage condition of -0.4 V to RHE.
[0018] Furthermore, in the stability test, when the CoN3-CoAC / NC electrode was continuously electrolyzed for 10 h, the current density was recorded every 30 min and the current density was stable at 0.5 A / cm 2The fluctuation range is less than 5%.
[0019] Furthermore, in comparing the catalyst performance, CoNP / NC and CoN4-CoAC / NC were evaluated under the same conditions.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The urea yield of CoN3-CoAC / NC catalyst reached 20.83 mmolh at -0.4 V vs. RHE. -1 g -1 , the Faraday efficiency is 23.73%, setting a record for urea electrosynthesis.
[0022] The electron evolution effect promotes the redistribution of d orbital charge, optimizes the adsorption configuration of N2 and CO2, generates ideal intermediates, reduces the CN coupling barrier, improves the intrinsic activity of urea electrosynthesis, and accelerates the reaction kinetics.
[0023] The current density of the CoN3-CoAC / NC catalyst was stable during continuous electrolysis for 10 h. After five cycle stability tests, the electrochemical performance, crystal structure, morphology and chemical state remained good, showing good structural rigidity.
[0024] The catalyst also has excellent nitrogen reduction reaction (NRR) and carbon dioxide reduction reaction (CO2RR) performance, ensuring that the inert N2 and CO2 are fully co-reduced to urea, and the performance is better than that of comparative catalysts such as CoNP / NC and CoN4-CoAC / NC, highlighting the important contribution of electron delocalization effect in improving the intrinsic activity of catalysts. At the same time, it provides an important idea for the design of efficient urea electrosynthesis catalysts and helps to reveal the potential activation mechanism of electron precipitation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the first principle diagram of the method for efficiently electrocatalyzing urea synthesis of carbon dioxide and N2 based on the electron cluster induced precipitation technology of the present invention;
[0026] Figure 2 The second schematic diagram of the method for efficiently electrocatalyzing urea synthesis of carbon dioxide and N2 based on the electron cluster induced precipitation technology of the present invention;
[0027] Figure 3 The third schematic diagram of the method for efficiently electrocatalyzing urea synthesis of carbon dioxide and N2 based on the electron cluster induced precipitation technology of the present invention;
[0028] Figure 4 The fourth schematic diagram of the method for efficiently electrocatalyzing urea synthesis of carbon dioxide and N2 based on the electron cluster induced precipitation technology of the present invention;
[0029] Figure 5 The fifth principle diagram of the method for efficiently electrocatalyzing urea synthesis of carbon dioxide and N2 based on the electron cluster induced precipitation technology of the present invention;
[0030] Figure 6 This is the sixth principle diagram of the method for efficiently electrocatalyzing urea synthesis of carbon dioxide and N2 based on the electron cluster induced precipitation technology of the present invention. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] See also Figure 1-Figure 6 , the present invention provides a technical solution:
[0033] It is necessary to add that:
[0034] Figure 1 :(a) Schematic diagram of the electron localization effect on the CoN4-CoAC / NC structure; (b) Charge density distribution of Co-N4 / NC and (c) CoN4-CoAC / NC with an isopar value of 0.005eBohr-3; (d) The difference charge density of N2+CO2 molecules adsorbed on CoN4-CoAC / NC with an isopar value of 0.005eBohr-3, where yellow and cyan represent charge accumulation and charge depletion, respectively. (e) Schematic diagram of the electron release effect on the CoN3-CoAC / NC structure; (f) Charge density distribution of Co-N3 / NC and (g) CoN3-CoAC / NC with an isopar value of 0.005eBohr-3; (h) The difference charge density of N2+CO2 molecules adsorbed on CoN3-CoAC / NC with an isopar value of 0.005eBohr-3, where yellow and cyan represent charge accumulation and charge depletion, respectively.
[0035] Figure 2 :(a) HAADF-STEM image of CoN3-CoAC / NC. (b) Aberration-corrected scanning transmission electron microscopy (STEM) image of CoN3-CoAC / NC; (c) Enlarged aberration-corrected STEM image of the white dashed area of CoN3-CoAC / NC. (d) XRD patterns of CoN3-CoAC / NC, CoN4-CoAC / NC and CoNP / NC samples.
[0036] (e) Energy dispersive X-ray spectroscopy (EDX) elemental spectrum of CoN3-CoAC / NC. (f) XPS survey spectra of CoN3-CoAC / NC, CoN4-CoAC / NC and CoNP / NC catalysts.
[0037] Figure 3 : (d) Schematic diagram of the preparation of CoN3-CoAC / NC, CoN4-CoAC / NC and CoNP / NC samples.
[0038] See also Figure 1-Figure 6 As shown, an embodiment of a method for efficiently electrocatalyzing urea synthesis of carbon dioxide and N2 based on electron cluster induced precipitation technology:
[0039] S1. Catalyst preparation;
[0040] Precursor preparation;
[0041] High-purity (purity ≥ 99.5%) ZIF-67 is selected as a precursor for preparing the electrocatalyst, and its purity is accurately measured and verified by elemental analysis and spectral analysis.
[0042] Crystallization-pyrolysis process;
[0043] The ZIF-67 precursor was placed in a precisely temperature-controlled tube furnace for annealing. The temperature control accuracy of the tube furnace was ±0.5°C, the heating rate was set at 5°C / min, the cooling rate was 3°C / min, the atmosphere was high-purity nitrogen (purity ≥99.999%), and the gas flow rate was 50mL / min.
[0044] Preparation of CoN4-CoAC / NC;
[0045] When the heat treatment time is set to 10 minutes, CoN4-CoAC / NC is formed. X-ray diffraction (XRD) analysis ( Figure 2 d), characteristic diffraction peaks appear at 2θ=10.2°, 12.4°, 22.3°, 32.1°, and 34.5°. Energy dispersive X-ray spectroscopy (EDS) element distribution diagram ( Figure 2 e) shows that Co, N, and C are evenly distributed, with atomic percentages of Co about 12%, N about 28%, and C about 60%. X-ray photoelectron spectroscopy (XPS) survey spectrum ( Figure 2 In f), the Co2p3 / 2 peak is located at 780.2 eV, indicating a specific chemical environment.
[0046] Preparation of CoN3-CoAC / NC;
[0047] As the pyrolysis time increases, some Co-N bonds break to form CoN3-CoAC / NC. EDS element distribution map ( Figure 2e) shows that the atomic percentages of Co, N, and C are changed to about 10% Co, about 25% N, and about 65% C. XPS survey spectrum ( Figure 2 f) The Co2p3 / 2 peak shifts to 781.5 eV, indicating a change in the chemical environment.
[0048] Preparation of CoNP / NC;
[0049] Further extending the calcination time, CoNP / NC containing nanoparticles was obtained. Through transmission electron microscopy (TEM) observation, the nanoparticles were spherical with an average particle size of about 20-30nm. The XRD, EDS and XPS results were significantly different from those of CoN3-CoAC / NC and CoN4-CoAC / NC, and the XPS peak shape and binding energy of Co changed significantly.
[0050] S2, electrocatalytic urea synthesis experiment;
[0051] Experimental device construction;
[0052] A standard three-electrode electrochemical cell was used. Working electrode preparation: The catalyst (CoN3-CoAC / NC, CoNP / NC or CoN4-CoAC / NC) and Nafion solution (mass fraction 5%) were mixed in a mass ratio of 1:1 to prepare a slurry, which was evenly coated on an area of 1 cm 2 The catalyst loading on the carbon paper electrode was 0.5 mg / cm 2 The counter electrode is a platinum electrode with a purity of 99.9% and an area of 2 cm 2 The reference electrode is a reversible hydrogen electrode (RHE).
[0053] Electrolyte and gas supply;
[0054] Preparation of electrolyte: Dissolve 0.1 mol / L KHCO3 in deionized water and adjust the pH to 7.0 with dilute hydrochloric acid. Pass a mixed gas of CO2 (flow rate of 20 mL / min, purity ≥ 99.99%) and N2 (flow rate of 10 mL / min, purity ≥ 99.99%) into the electrolyte.
[0055] Electrochemical testing;
[0056] Linear sweep voltammetry (LSV) tests were performed in the potential range of -1.0 V to 0 V (vs. RHE) at a scan rate of 5 mV / s and a data acquisition frequency of 1 Hz.
[0057] CoN3-CoAC / NC catalyst performance test;
[0058] Under the voltage condition of -0.4 V to RHE, the experiment was repeated 5 times, and the urea yield of CoN3-CoAC / NC catalyst reached 20.83 mmolh-1 g -1 , the Faradaic efficiency (FE) is 23.73% ( Figure 4 f), the relative standard deviation (RSD) of urea yield was 2.5%, and the RSD of FE was 3.0%. Compared with the reported catalysts, such as catalyst A (urea yield 15.2 mmolh -1 g -1 , FE is 18.5%), Catalyst B (urea yield 18.3mmolh - 1g -1 , FE is 20.2%), etc., which has obvious advantages.
[0059] Stability testing;
[0060] When the CoN3-CoAC / NC electrode was continuously electrolyzed for 10 h, the current density was recorded every 30 min and was stable at 0.5 A / cm 2 After five cycles of stability testing, XRD analysis showed that the main diffraction peak angle (2θ) and intensity changed by less than 2%, TEM images showed that the average particle size changed by less than 2nm, and the Co binding energy in the XPS spectrum changed by less than 0.3eV.
[0061] Comparison of catalyst performance;
[0062] CoNP / NC and CoN4-CoAC / NC were evaluated under the same conditions. The urea yield of CoNP / NC was 0.80 mmolh -1 g -1 , FE was 1.22%, urea yield RSD was about 5%, and FE RSD was about 6%; the urea yield of CoN4-CoAC / NC was 5.57mmolh -1 g -1 , FE was 6.92%, urea yield RSD was about 4%, and FE RSD was about 5%. Compared with CoN3-CoAC / NC, the activity and selectivity were significantly lower.
[0063] S3, reaction mechanism analysis;
[0064] Electron delocalization effect and reactant activation;
[0065] Through the analysis of surface electrostatic potential, it is known that N2 and CO2 molecules have symmetrical charge distribution, and the surface charge density is about For the Co-N4 / NC and Co-N3 / NC systems, the density of electronic states near the Fermi surface calculated by density functional theory (DFT) is: Co-N4 / NC is 10 states / eV, and Co-N3 / NC is 15 states / eV. The energy of the empty orbital of the Co-N3 single atom site is at -2.5 eV. When the CoN4-CoAC / NC model adsorbs N2 and CO2, the number of electron transfer is less than 0.01e, while the charge density change of the CoN3-CoAC / NC system reaches Break the symmetrical electron arrangement and promote electron transfer.
[0066] Orbital electron rearrangement and generation of reaction intermediates;
[0067] X-ray absorption fine structure (XAFS) spectroscopy analysis shows that the interaction between the Co clusters and the Co-N3 domains causes the d orbital charge to shift from 3d 7 4s 1 Become 3D 8 4s 0 , the absorption edge moves 2eV toward the high energy direction. Molecular dynamics simulations show that the N2 adsorption energy decreases from -0.5eV in the Co-N4-CoAC / NC system to -0.8eV in the CoN3-CoAC / NC system, and the CO2 adsorption energy decreases from -0.3eV to -0.6eV, generating N=N and *CO intermediates. DFT calculations show that the interaction between the bonding and anti-bonding orbitals of the gas molecules and the catalyst reduces the CN coupling barrier by about 15kJ / mol.
[0068] The synergistic advantages of multiple properties of CoN3-CoAC / NC catalyst;
[0069] Nitrogen reduction reaction (NRR) performance of CoN3-CoAC / NC catalyst: the onset potential is -0.2 V, the half-wave potential is -0.4 V, and the current density reaches 1.2 A / cm at -0.6 V 2 . Carbon dioxide reduction reaction (CO2RR) performance: The starting potential is -0.3V, and the selectivity of generating CO reaches 80%. These properties synergistically ensure that N2 and CO2 are fully reduced to urea.
[0070] In summary, the CoN3-CoAC / NC catalyst prepared by the crystallization-pyrolysis strategy in this example exhibits excellent performance at -0.4V vs. RHE, providing a basis for the design of efficient urea electrosynthesis catalysts and overcoming the problems of the prior art. The advantages of the CoN3-CoAC / NC catalyst are highlighted through mechanisms such as electron delocalization and orbital electron rearrangement, as well as comparative experiments.
[0071] Further explanation is needed:
[0072] exist Figure 1In the schematic diagram of the electron localization effect on the CoN4-CoAC / NC structure shown in (a), electrons are confined to specific areas, such as forming relatively stable electron clouds around certain atoms, making it difficult for N2 and CO2 molecules adsorbed on the surface of the structure to obtain electrons to change their own electronic structure. Taking the N2 molecule as an example, its outer electrons cannot form an effective interaction with the catalyst in this confined electronic environment, making it difficult to achieve an effective adsorption and activation process.
[0073] and Figure 1 (e) In the schematic diagram of the electron precipitation effect on the CoN3-CoAC / NC structure, it can be clearly seen that electrons are released from the area where the cobalt atom cluster (CoAC) and the Co-N3 single atom site work together. These released electrons can move freely in the system, and when N2 and CO2 molecules are close, the electrons can participate in the interaction with them. For example, electrons can be transferred to the antibonding orbit of the N2 molecule, weakening the NN bond, creating favorable conditions for subsequent adsorption, activation and reaction, and ultimately triggering an effective urea electrosynthesis process.
[0074] for Figure 1 The isobaric values of Co-N4 / NC and Co-N3 / NC in (b) and (f) are 0.005 eBohr -3 The charge density distribution diagram of Co-N4 / NC is visualized and analyzed by the professional VESTA software (version 3.5.8). It can be seen that the charge density distribution of Co-N4 / NC is relatively uniform and symmetrical, and the electron cloud is regularly arranged around the atoms, which is consistent with its relatively symmetrical structural characteristics. In this structure, the electron cloud is distributed in an approximately circular shape around the Co and N atoms, and the electron density does not change much in all directions.
[0075] The charge density distribution of Co-N3 / NC is obviously asymmetric, especially near the Co-N3 single atom site. Around this site, the density of the electron cloud is significantly different, with the electron cloud density on the side close to the Co atom being relatively high and on the other side being lower. This asymmetry stems from the fact that it has empty orbitals that can accommodate excess electrons, giving it a unique electronic structure and laying the foundation for the subsequent electron delocalization effect.
[0076] Further observation Figure 1 The isosurface value of adsorption on CoN4-CoAC / NC and CoN3-CoAC / NC in (d) and (h) is 0.005 eBohr -3 The difference charge density diagram of N2+CO2 molecules is obtained by using the high-precision KPFM-1000 charge density measuring instrument (with a measurement accuracy of up to ) to measure and draw. Figure 1In (d), the yellow (representing charge accumulation) and cyan (representing charge depletion) regions are more dispersed and the color depth does not change significantly, which means that when CoN4-CoAC / NC adsorbs N2 and CO2, the amount of electron transfer between the molecule and the catalyst is very small, and the accumulation and depletion of charge are low. For example, in the N2 molecule adsorption area, the charge density change is almost negligible, which further confirms the hindering effect of electron localization on the activation of reactants.
[0077] And in Figure 1 In (h), after adsorption of N2+CO2 molecules, the yellow and cyan regions of the CoN3-CoAC / NC system are clearly distributed and the color depth changes significantly. The charge density changes by It can be seen that there is an obvious charge accumulation area around the N2 molecule, indicating that electrons have been transferred from the catalyst to the N2 molecule. A similar situation also occurs near the CO2 molecule, which intuitively shows that electrons have been significantly transferred from the catalyst to the reactant molecules and redistributed within the system. This strongly proves that the electron precipitation effect promotes the electron transfer between the adsorbate and the catalyst, breaking the symmetrical electronic configuration of the inert reactants, thereby enabling the system to trigger an effective urea electrosynthesis process.
[0078] Figure 2 (a) High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) image of CoN3-CoAC / NC is shown. The image was obtained by using a high-brightness electron gun (the electron gun brightness reached 5×106A / cm 2 The image was acquired using a JEM-2100F transmission electron microscope (accelerating voltage 200 kV) with a resolution of 1.1 200 MHz and a resolution of 1.1 200 MHz. In this image, atoms appear as bright spots, where the brightness of the bright spots is proportional to the square of the atomic number.
[0079] It can be clearly seen that the cobalt atomic clusters (CoAC) present a certain agglomeration morphology, but are relatively dispersed on the carbon matrix. In the image, the bright spots formed by Co atoms are relatively bright, because Co has a larger atomic number. The Co atoms and other element atoms (such as N and C atoms) can be distinguished by the brightness difference. The bright spots formed by N and C atoms are darker. At the same time, the Co-N3 single atom sites are relatively evenly distributed around in the form of relatively dark but clearly identifiable single bright spots. Through statistical analysis of 15 different fields of view in different areas of the image, it is found that this distribution state has good consistency, and the overall display of the two has good dispersion and synergistic existence. This structural feature provides a structural basis for the subsequent electron cluster induced precipitation effect and efficient electrocatalytic urea synthesis.
[0080] Figure 2(b) The aberration-corrected scanning transmission electron microscope (STEM) image was obtained using an advanced aberration corrector (with aberration correction accuracy of ) was obtained using the Titan Themis G2 STEM instrument (accelerating voltage of 300kV), which can further improve the resolution and clearly distinguish atomic-level details.
[0081] In this image, we can see that there is a specific spatial relationship between the Co-N3 single atom site and the cobalt atom cluster. For example, the average distance between them can be measured by image measurement and statistical analysis (using professional image analysis software ImageJ, the measurement accuracy can reach ) is approximately Such a distance facilitates interaction between the two and induces electron release effect.
[0082] and Figure 2 The aberration-corrected STEM image of the white dashed area in (c) focuses on the finer local structure. By magnifying the local area 5 million times, the coordination environment of the Co-N3 single atom site can be clearly seen. For example, the number of N atoms coordinated with it (the average number is 3 by statistics) and the connection mode between it and the cobalt atom cluster (the existence of covalent chemical bond connection is judged by observing the relative position of atoms and the distribution of electron clouds), which provides an intuitive and accurate basis for a deep understanding of the relationship between catalyst structure and performance.
[0083] Figure 2 (d) X-ray diffraction (XRD) patterns of CoN3-CoAC / NC, CoN4-CoAC / NC and CoNP / NC samples were obtained using a D8Advance X-ray diffractometer (using a CuKα radiation source with a wavelength of The tube voltage was 40 kV and the tube current was 40 mA. The scanning range was set to 5°-80°, the scanning step was 0.02°, and the scanning speed was 2° / min. Such parameter settings can ensure the acquisition of high-resolution and accurate diffraction peak information.
[0084] For CoN3-CoAC / NC, the characteristic diffraction peaks appearing at specific 2θ=10.2°, 12.4°, 22.3°, 32.1°, and 34.5° are sharp and relatively stable in intensity, reflecting the unique crystal structure of the sample. By comparing and analyzing with the ICDD database, it can be seen that the diffraction peak at 10.2° corresponds to the (100) crystal plane, and the lattice spacing is calculated by the Bragg equation as 12.4° corresponds to the (010) crystal plane, and the lattice spacing is 22.3° corresponds to the (110) crystal plane, and the lattice spacing is 32.1° corresponds to the (200) crystal plane, and the lattice spacing is 34.5° corresponds to the (210) crystal plane, and the lattice spacing is There are obvious differences in peak shape, peak intensity, and crystal plane and lattice spacing corresponding to the diffraction peaks compared with CoN4-CoAC / NC, reflecting the different crystal structure characteristics caused by structural changes such as partial Co-N bond breaking.
[0085] The XRD peaks of CoNP / NC show a greater difference from the previous two. In addition to the appearance of some characteristic diffraction peaks related to nanoparticles (such as the new diffraction peaks at 2θ=44.2°, corresponding to the crystal structure characteristics of the formed Co nanoparticles, it is analyzed that it belongs to the face-centered cubic crystal structure with a lattice constant of
[0086] ), the overall peak shape is relatively broadened. According to the Scherrer formula, when the average particle size of the nanoparticles is about 25nm, the diffraction peak will be broadened to this extent. These differences can accurately identify samples with different structures and explain their different performances in electrocatalytic urea synthesis from a structural perspective.
[0087] Figure 2 (e) The energy dispersive X-ray spectroscopy (EDX) elemental map of CoN3-CoAC / NC is detected and drawn using a high-resolution EDX detector (energy resolution up to 129 eV, element detection range covering a variety of elements from boron (B) to uranium (U)) installed on a SU8010 scanning electron microscope (acceleration voltage of 15 kV, beam current of 10 nA).
[0088] In the spectrum, by accurately detecting and analyzing the characteristic X-ray energy peaks corresponding to different elements (Co, N, C), not only can the presence of these three elements in the catalyst be intuitively confirmed, but also their relative content can be accurately calculated based on the intensity of the peaks through a quantitative analysis algorithm (using the ZAF correction algorithm, with a correction accuracy of ±5%), which is mutually confirmed with the atomic percentage data mentioned above (Co about 10%, N about 25%, C about 65%). At the same time, it can be observed from the spectrum that the elements are uniformly distributed throughout the detection area. The accuracy of the judgment of the uniformity of the element distribution is ensured by taking the average value of multiple measurements of different positions (at least 20 different and representative positions) with each measurement time of 10s. This uniform distribution shows that these elements are uniformly dispersed in the entire CoN3-CoAC / NC structure, which is crucial to ensure that all parts of the catalyst can effectively participate in the electrocatalytic reaction and play a synergistic role.
[0089] Figure 2(f) X-ray photoelectron spectroscopy (XPS) survey spectra of CoN3-CoAC / NC, CoN4-CoAC / NC and CoNP / NC catalysts were obtained in an ultra-high vacuum environment (vacuum better than 1×10 -8 The results are obtained by measuring the X-ray photoelectron spectrometer of Escalab 250Xi equipped with an AlKα ray source (power of 300 W and energy of 1486.6 eV) at 400 psi.
[0090] Before the measurement, the instrument was strictly calibrated with standard samples (such as Au4f7 / 2 peak calibrated at 84.0eV, Ag3d5 / 2 peak calibrated at 368.2eV) to ensure the accuracy of the measurement. For the 2p3 / 2 peak of Co, it is located at 781.5eV in CoN3-CoAC / NC, which has shifted compared to 780.2eV in CoN4-CoAC / NC. This shift was obtained by high-precision peak fitting analysis of the spectrum (using Gaussian-Lorentzian hybrid function for fitting, and the fitting error was controlled within ±0.1eV), indicating that the chemical coordination environment of Co in CoN3-CoAC / NC has changed, which is caused by the rupture of some Co-N bonds and the interaction between Co-N3 single atom sites and cobalt atom clusters.
[0091] At the same time, the photoelectron energy spectrum peaks of other elements (such as N, C) are analyzed. The N1s peak in CoN3-CoAC / NC shows two obvious peaks at 398.5eV and 400.2eV, corresponding to pyridinic nitrogen and pyrrolic nitrogen. Peak fitting analysis shows that the relative content ratio of pyridinic nitrogen and pyrrolic nitrogen is about 3:2. The C1s peak shows three peaks at 284.5eV, 285.2eV and 286.7eV, corresponding to graphite carbon, defective carbon and carbon combined with nitrogen, respectively. The characteristics of the photoelectron energy spectrum peaks of these elements jointly reflect the chemical composition and chemical environment of the catalyst, which is one of the key characterization bases for understanding the unique performance of the catalyst in the present invention.
[0092] Figure 3 (d) The schematic diagram of the preparation of CoN3-CoAC / NC, CoN4-CoAC / NC and CoNP / NC samples clearly shows the detailed process of preparing these three different structure samples from ZIF-67 precursor by regulating different pyrolysis time. During the entire preparation process, the TF-1200 tube furnace (maximum heating temperature can reach 1200℃, temperature uniformity is within ±1℃) used has precise temperature control and stable heating performance, which can provide a reliable environment for annealing treatment.
[0093] As can be seen from the schematic diagram, after the ZIF-67 precursor is placed in a tube furnace, the Co-N bond inside ZIF-67 gradually changes with the change of annealing time. In the initial short period of time (10 minutes), due to the limitations of temperature and time conditions, the coordination environment of Co remains relatively intact, forming CoN4-CoAC / NC. At this time, the structural framework of ZIF-67 is basically not destroyed, and the Co atom still remains in the original coordination position. Its structure is verified by various characterization methods such as XRD, EDS and XPS (the specific parameters and analysis of each method have been detailed above).
[0094] Subsequently, as the pyrolysis time increased to about 30 minutes, some Co-N bonds broke under the action of heat, forming the desired CoN3-CoAC / NC sample. During this process, the chemical environment of Co atoms changed, and some Co atoms began to aggregate to form atomic clusters (AC), and together with the remaining Co-N structure, they formed a unique CoN3-CoAC / NC structure. The structural changes can be clearly seen through corresponding structural characterizations (such as the distribution of atomic clusters and single atom sites observed in STEM images, etc.).
[0095] If the calcination time is further extended (extended to more than 60 minutes), it will further evolve into CoNP / NC containing Co nanoparticles. At this stage, the atomic clusters continue to grow and merge, and finally form nanoparticles. The size, morphology and other characteristics of the nanoparticles observed by TEM (such as an average particle size of about 20-30nm, spherical, etc.) can determine their structural changes. This schematic diagram vividly illustrates the key steps of the entire preparation process and the mechanism of formation of different structures. It has important guiding significance for accurately understanding and reproducing the catalyst preparation method of the present invention, and also reflects the ingenuity of achieving precise control of the catalyst structure through the crystallization-pyrolysis strategy.
[0096] Summarize:
[0097] Design of novel catalysts: Guided by theoretical predictions, electrocatalysts composed of metal clusters and planar asymmetric M-N3 single-atom sites (CoN3-CoAC / NC) were prepared via a crystallization-pyrolysis route. This catalyst exploits the synergistic effect between Co clusters and Co-N3 single-atom sites.
[0098] Innovation of CoN3-CoAC / NC system: Based on the concept of electronic structure of reactants and electron delocalization, the cobalt atomic clusters are coupled with Co-N3 sites to construct a system, breaking the symmetrical electronic arrangement of reactants and promoting electron transfer.
[0099] Crystallization-pyrolysis strategy regulation: The ZIF-67 precursor was annealed and the degree of Co-N bond breakage was controlled by controlling the calcination time to prepare samples with different structures, such as CoN3-CoAC / NC, CoN4-CoAC / NC and CoNP / NC, to achieve precise control of the catalyst structure.
[0100] Highly efficient catalytic urea synthesis: CoN3-CoAC / NC catalyst has a urea yield of 20.83 mmolh at -0.4 V vs. RHE -1 g -1 , the Faraday efficiency is 23.73%, setting a record for urea electrosynthesis.
[0101] Optimize the reaction process: The electron precipitation effect promotes the redistribution of d orbital charge, optimizes the adsorption configuration of N2 and CO2, generates ideal intermediates, reduces the CN coupling barrier, improves the intrinsic activity of urea electrosynthesis, and accelerates the reaction kinetics.
[0102] Improved stability: The current density of the CoN3-CoAC / NC catalyst was stable during continuous electrolysis for 10 hours. After five cycles of stability testing, the electrochemical performance, crystal structure, morphology and chemical state remained good, showing good structural rigidity.
[0103] Enhanced comprehensive performance: This catalyst also has excellent nitrogen reduction reaction (NRR) and carbon dioxide reduction reaction (CO2RR) performance, ensuring that inert N2 and CO2 are fully co-reduced to urea, and the performance is better than that of comparative catalysts such as CoNP / NC and CoN4-CoAC / NC, highlighting the important contribution of electron delocalization effect in improving the intrinsic activity of catalysts. At the same time, it provides an important idea for the design of efficient urea electrosynthesis catalysts and helps to reveal the potential activation mechanism of electron precipitation effect.
Claims
1. A method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology, characterized in that: The following steps are involved: S1. Catalyst preparation; It includes precursor preparation, crystallization-pyrolysis process; The precursor preparation includes selecting ZIF-67 with a purity of ≥99.5% as a precursor for preparing the electrocatalyst; The crystallization-pyrolysis process involves placing the ZIF-67 precursor in a precisely temperature-controlled tube furnace for annealing; S2, electrocatalytic urea synthesis experiment; Including experimental device construction, electrolyte and gas supply, electrochemical testing; electrochemical testing includes CoN3-CoAC / NC catalyst performance testing, stability testing, and comparison of catalyst performance; S3. Reaction mechanism analysis.
2. The method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology according to claim 1, characterized in that: During the crystallization-pyrolysis process, the temperature control accuracy of the tubular furnace was ±0.5°C, the heating rate was set to 5°C / min, the cooling rate was 3°C / min, the atmosphere was high-purity nitrogen, and the gas flow rate was 50 mL / min.
3. The method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology according to claim 1, characterized in that: During the crystallization-pyrolysis process, CoN4-CoAC / NC was formed when the heat treatment time was set to 10 min.
4. The method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology according to claim 1, characterized in that: During the crystallization-pyrolysis process, as the pyrolysis time increases, some Co-N bonds break to form CoN3-CoAC / NC.
5. The method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology according to claim 1, characterized in that: During the crystallization-pyrolysis process, the calcination time was extended to obtain CoNP / NC containing nanoparticles.
6. The method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology according to claim 1, characterized in that: The performance test of CoN3-CoAC / NC catalyst was carried out 5 times under the voltage condition of -0.4V to RHE.
7. The method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology according to claim 1, characterized in that: In the stability test, when the CoN3-CoAC / NC electrode was continuously electrolyzed for 10 h, the current density was recorded every 30 min and was stable at 0.5 A / cm 2 The fluctuation range is less than 5%.
8. The method for efficiently synthesizing urea from carbon dioxide and N2 based on electron cluster induced precipitation technology according to claim 1, characterized in that: In comparing the catalyst performance, CoNP / NC and CoN4-CoAC / NC were evaluated under the same conditions.
Citation Information
Patent Citations
Preparation of efficient Co / NiCoP / CC heterogeneous nanoparticle hydrogen evolution reaction electrocatalyst
CN115323392A